BREASTFEEDING BARRIERS THAT CONTRIBUTE TO EXCLUSIVE BREASTFEEDING FAILURE - Ade Saputra Nasution; Siti Umrana; Ida Nuraida; Devia Lydia Putri (IAKMI South Tangerang Branch, 2024)
Background: Breast milk is the best nutrition for children, but many children in Indonesia do not receive exclusive breastfeeding. According to SSGI data, only 48.58% of babies in Bogor district are exclusively breastfed. This is due to various obstacles in the breastfeeding process, which can stem from both maternal and infant factors. If this situation continues, the child's nutritional needs may not be adequately met. Objective: To determine the most dominant factor in exclusive breastfeeding failure. Method: A cross-sectional study was conducted with a random sample of 182 individuals in Bogor Regency. Data were analyzed using the chi-square test and logistic regression. Result: There was no significant association between exclusive breastfeeding failure and mothers having difficulty managing time between work and breastfeeding, difficulties in positioning the baby, or experiencing nipple blisters (p≤0.05). Additionally, no significant associations were found between exclusive breastfeeding failure and infants remaining fussy even after breastfeeding, mothers experiencing depression during initial breastfeeding, feeling embarrassed while breastfeeding, infants having difficulty breastfeeding, or mothers experiencing swollen breasts (p>0.05). Conclusion: Infants who remained fussy despite breastfeeding were found to be the most dominant factor contributing to exclusive breastfeeding failure, with an odds ratio (OR) of 2.308.